Law Enforcement of the Crime of Trafficking of Imported Drugs That Do Not Have a Distribution Permit - Aryzha Fitri Founda Wahyudi; Bastianto Nugroho; Supolo Setyo Wibowo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The research aims to find out what efforts can be made to prevent losses and what liability must be borne by business actors for consumers for the use of drugs. The research method using the normative juridical method is to describe based on legal provisions and legal facts that apply in the wider community and the problems discussed are based on the facts that occur in society. The results of research on drug business actors are liable for consumer losses. Lawsuits can be filed based on default or unlawful acts. Lawsuits based on defaults are very weak because they require a contractual relationship between the parties so that only parties bound by a contract can sue each other. Thus, the producer can refuse responsibility on the grounds that there is no contractual relationship between the parties. However, the producer cannot simply escape responsibility because there are still other legal remedies, namely lawsuits for unlawful acts that do not require a contractual relationship between consumers and business actors. The proof system used in this business actor's liability is regulated in Article 28 of Law Number 8 of 1999, namely using a reverse proof system. Consequently, it is the business actor who proves whether there is a mistake in him or not.